Ingested Capsaicinoids Can Prevent Low-Fat/High-Carbohydrate diet and High-Fat Diet-Induced Obesity by Regulating the Expression of Genes for Metabolism - Şahin, Kazım; Orhan, Cemal; Tuzcu, Mehmet; Şahin, Nurhan; Ozdemir, Oguzhan; Juturu, Vijaya (Federation Amer Soc Exp Biol, 2016)
[Abstract Not Available]
Experimental Biology Meeting -- APR 02-06, 2016 -- San Diego, CA